Oh so sweet: a comparative investigation of retail market composition of sweetened and flavoured beverages in Singapore and Australia - Anastasiou, Kim (2023)
The consumption of sugar and non-nutritive sweeteners has been associated with poor health outcomes. The aim of this paper was to provide a comparison of the range of sweetened or flavoured beverages between two high-income countries in the Asia-Pacific region: Australia and Singapore. Following the FoodTrackTM methodology, nutrition, labelling, and price data were collected from major Australian and Singaporean supermarket chains and convenience stores. The nutrient profiles of products were tested for differences using Kruskal−Wallis and Mann−Whitney U tests. The greatest number of products collected in Australia were from the ‘carbonated beverages’ category (n = 215, 40%), and in Singapore the greatest number of products were from the ‘tea and coffee ready-to-drink’ category (n = 182, 35%). There were more calorically sweetened beverages in Singapore compared with Australia (n = 462/517 vs. n = 374/531, p < 0.001). For calorically sweetened products, the median energy of Singaporean products was significantly higher than Australian products (134 kJ vs. 120 kJ per 100 mL, p = 0.009). In Australia, 52% of sweetened or flavoured beverages displayed a front-of-pack nutrient signposting logo, compared with 34% of sweetened or flavoured beverages in Singapore. These findings also indicate that the consumption of just one serving of calorically sweetened carbonated beverages or energy drinks would exceed the WHO maximum daily free sugar recommendations.